Wilson – Konovalov Disease: Clinical Cases with Different Manifestations and Outcomes - O. V. Samodova; G. P. Smirnova; E. A. Krieger (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Аim: to describe clinical cases of Wilson – Konovalov disease in pediatric patients.Key points. The first clinical case demonstrates the manifestation of Wilson – Konovalov disease with unexplained mild elevation of aminotransferases at the age of 6 years. Despite the persistent hyperenzymemia, no additional laboratory tests were prescribed. At the age of 10, the patient showed signs of liver failure and neurological symptoms. Laboratory and instrumental examination enabled to diagnose Wilson – Konovalov disease at the stage of liver cirrhosis. The diagnosis was confirmed at the Federal medical center. The diagnosis was delayed and made 4 years after the hyperenzymemia was first revealed. The relief of clinical signs was observed after the orthotopic transplantation of the right lobe of the liver from a living related donor. The patient was under surveillance for 10 years after the transplantation.The second clinical case shows another variant of the course of the Wilson – Konovalov disease manifested as an acute hepatitis. To clarify the etiology of the disease, the patient was hospitalized. In 2 weeks, the patient developed symptoms of acute liver failure, progressive hemorrhagic syndrome, acute hepatic encephalopathy. Death from fulminant hepatitis occurred in 3 weeks after the disease onset after the disease onset.Conclusion. Healthcare workers should be aware of clinical signs of Wilson – Konovalov disease. Screening for the disease is recommended for children with an unexplained increase of liver transaminases, acute liver failure, chronic hepatitis and liver cirrhosis.